Developing and evaluating an e-learning and e-assessment tool for organic chemistry in higher education - Schuessler, Katrin; Striewe, Michael; Pueschner, Daniel; Luetzen, Arne; Goedicke, Michael; Giese, Michael; Walpuski, Maik (Frontiers in Education, 2024)
A convincing e-learning system for higher education should offer adequate usability and not add unnecessary (extraneous) cognitive load. It should allow teachers to switch easily from traditional teaching to flipped classrooms to provide students with more opportunities to learn and receive immediate feedback. However, an efficient e-learning and technology-enhanced assessment tool that allows generating digital organic chemistry tasks is yet to be created. The Universities of Bonn and Duisburg-Essen are currently developing and evaluating an e-learning and technology-enhanced assessment tool for organic chemistry. This study compares the effectiveness of traditional paperpencil-based and digital molecule-drawing tasks in terms of student performance, cognitive load, and usability-factors that all contribute to learning outcomes. Rasch analysis, t-tests, and correlation analyses were used for evaluation, revealing that the developed system can generate digital organic chemistry tasks. Students performed equally well on simple digital and paper-pencil moleculedrawing tasks when they received an appropriate introduction to the digital tool. However, using the digital tool in three of four studies imposes a higher extraneous cognitive load than using paper and pencil. Nevertheless, the students rated the tool as sufficiently usable. A significant negative correlation between extraneous load and tool usability was found, suggesting room for improvement. We are currently concentrating on augmenting the functionality of the new e-learning tool to increase its potential for automatic feedback, even for complex tasks such as reaction mechanisms.